Development assistance for health: what criteria do multi- and bilateral funders use?. Issue 2 (23rd March 2017) - Ottersen, Trygve; Kamath, Aparna; Moon, Suerie; Martinsen, Lene; Røttingen, John-Arne
Abstract: After years of unprecedented growth in development assistance for health (DAH), the system is challenged on several fronts: by the economic downturn and stagnation of DAH, by the epidemiological transition and increase in non-communicable diseases, and by the economic transition and rise of the middle-income countries. This raises questions about which countries should receive DAH and how much, and, fundamentally, what criteria that promote fair and effective allocation. Yet, no broad comparative assessment exists of the criteria used today. We reviewed the allocation criteria stated by five multilateral and nine bilateral funders of DAH. We found that several funders had only limited information about concrete criteria publicly available. Moreover, many funders not devoted to health lacked specific criteria for DAH or criteria directly related to health, and no funder had criteria directly related to inequality. National income per capita was emphasised by many funders, but the associated eligibility thresholds varied considerably. These findings and the broad overview of criteria can assist funders in critically examining and revising the criteria they use, and inform the wider debate about what the optimal criteria are.